A method for preparing glass-ceramics using coal gangue
Through ball milling and high-temperature treatment of coal gangue, epoxy modified carbon nanotubes and hyperbranched refiners, microcrystalline glass with high density, excellent mechanical strength and chemical stability were prepared, which solved the problem of insufficient density of existing microcrystalline glasses and expanded its application scope.
Patent Information
- Application Number
- CN202411748867.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The existing microcrystalline glass prepared by coal gangue is insufficient in density, resulting in low mechanical strength and poor chemical stability, limiting its application in high-strength and acid-base environments.
After ball milling coal gangue, epoxy modified carbon nanotubes, hyperbranched refined agent and anhydrous ethanol in a ball mill, it is vacuum dried and melted at high temperature, and then cast and molded and annealed. Finally, it is insulated multiple times at high temperature to improve the density and stability of the microcrystalline glass.
This method significantly improves the density, mechanical strength and chemical stability of microcrystalline glass, making it more widely used in high-strength and acid-base environments, while reducing production costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of coal gangue, and in particular to a method for preparing microcrystalline glass by utilizing coal gangue. Background Art
[0002] Gangue is a kind of mining solid waste discharged during coal mining and washing. It has lower carbon content and calorific value than ordinary coal and has a hard texture. Large amounts of accumulated gangue not only occupy land resources, but also cause serious pollution to the environment. Glass-ceramics is a polycrystalline solid material made by controlled crystallization of basic glass. It has the advantages of high mechanical strength, good chemical stability, and high thermal stability. It is widely used in construction, electronics, chemical industry and other fields. Usually, gangue is rich in main chemical components such as Si, Al, and Fe, and its main mineral composition is quartz and feldspar, which is a necessary condition for the preparation of glass-ceramics. Therefore, the preparation of glass-ceramics with gangue as raw material can not only realize the transformation of gangue into treasure and resource utilization, but also avoid the safety and ecological environment problems caused by the large-scale storage of gangue, greatly improve the added value of gangue, and have significant environmental, economic and social benefits.
[0003] However, the density of the glass-ceramics prepared from coal gangue is insufficient, resulting in low mechanical strength and poor chemical stability, which limits its application in high-intensity and acid-base environments. Therefore, it is of great significance to develop a method for preparing glass-ceramics using coal gangue. Summary of the invention
[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a method for preparing microcrystalline glass using coal gangue, which solves the problem that the microcrystalline glass currently prepared using coal gangue has insufficient density, resulting in low mechanical strength and poor chemical stability, which limits its application in high-strength and acid-base environments.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing glass-ceramics using coal gangue comprises the following steps:
[0007] Step 1: Weigh 20-30 parts of coal gangue, 0.1-1.7 parts of epoxy-modified carbon nanotubes, 0.03-0.7 parts of hyperbranched refiner and 40-45 parts of anhydrous ethanol according to weight, and set aside;
[0008] Step 2: adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill, milling for 2-3 hours at a ball milling rate of 300-400 r / min, then placing in a vacuum drying oven, drying at a temperature of 75-80°C for 2-3 hours, then placing in a high-temperature furnace, melting at a temperature of 1400-1500°C for 2-3 hours, then pouring into a mold for casting, then annealing at a temperature of 550-600°C for 1-2 hours, and then cooling with the furnace to obtain a microcrystalline glass green body;
[0009] Step 3: Place the glass-ceramic green body in a high-temperature furnace, keep it at 650-700°C for 1-1.5h, then keep it at 950-1000°C for 1-1.5h, then keep it at 1200-1300°C for 1-1.5h, then cool it with the furnace to obtain glass-ceramic.
[0010] As a further solution of the present invention: the epoxy-modified carbon nanotubes are prepared by the following steps:
[0011] Step A1: adding multi-walled carbon nanotubes and nitric acid solution to a three-necked flask equipped with a stirrer and a thermometer, ultrasonically dispersing for 20-30 minutes at an ultrasonic frequency of 80-100kHz, and then stirring the reaction at a temperature of 75-80°C and a stirring rate of 300-400r / min for 3-4 hours. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is added to hydrogen peroxide and soaked for 10-12 hours at a temperature of 60-65°C, and then centrifuged. The precipitate is washed with anhydrous ethanol and distilled water for 2-3 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 80-90°C for 2-3 hours to obtain oxidized carbon nanotubes;
[0012] Step A2: Add the oxidized carbon nanotubes, epichlorohydrin and deionized water into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 55-60°C and continue stirring and reacting for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 55-60°C for 2-3 hours to obtain epoxy-modified carbon nanotubes.
[0013] As a further solution of the present invention: the usage ratio of the multi-walled carbon nanotubes and the nitric acid solution in step A1 is 2g:40-50mL.
[0014] As a further solution of the present invention: the average tube diameter of the multi-walled carbon nanotubes in step A1 is 80 nm, and the average tube length is 20 μm; the molar concentration of the nitric acid solution is 3-4 mol / L; and the mass fraction of the hydrogen peroxide is 30-35%.
[0015] As a further solution of the present invention: the dosage ratio of the oxidized carbon nanotubes, epichlorohydrin and deionized water in step A2 is 0.5g:4-5mL:40-50mL.
[0016] As a further solution of the present invention: the hyperbranched refiner is prepared by the following steps:
[0017] Step B1: Pyrene and nitrobenzene are added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and stirred for reaction for 20-30 minutes at a temperature of -5-0°C and a stirring rate of 300-400r / min, and then bromine is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the addition is completed, the temperature is raised to 120-125°C and the stirring reaction is continued for 8-10 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then added to anhydrous ethanol, and then centrifuged. The precipitate is washed with distilled water 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75°C for 2-3 hours to obtain intermediate 1;
[0018] Step B2: Sodium hydroxide and deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 15-25 min, and then intermediate 1, eugenol and N,N-dimethylformamide are added and the stirring reaction is continued for 1-2 h. The mixture is then heated to 55-60° C. and the stirring reaction is continued for 2-3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for stratification. The organic phase is washed with distilled water for 2-3 times, and then the solvent is removed by rotary evaporation to obtain intermediate 2;
[0019] Step B3: Add intermediate 2, diethanolamine and anhydrous tetrahydrofuran into a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, introduce nitrogen protection, stir the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 25-35 min, then heat to 45-50° C. and continue stirring the reaction for 6-8 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation to obtain intermediate 3;
[0020] Step B4: Add intermediate 3, 2,2-dihydroxymethylpropionic acid, p-toluenesulfonic acid and xylene to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 25-35min, then heat the temperature to 145-150°C and continue stirring the reaction for 8-10h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation, and then added to anhydrous methanol, followed by vacuum filtration. The filter cake is placed in a vacuum drying oven and dried at a temperature of 50-55°C for 4-5h to obtain a hyperbranched refiner.
[0021] As a further solution of the present invention: the usage ratio of the pyrene, nitrobenzene and bromine in step B1 is 10mmol:100-120mL:40-50mmol.
[0022] As a further scheme of the present invention: the usage ratio of the sodium hydroxide, deionized water, intermediate 1, eugenol and N,N-dimethylformamide in step B2 is 45-55mmol:100-120mL:10mmol:40-45mmol:70-80mL.
[0023] As a further scheme of the present invention: the usage ratio of the intermediate 2, diethanolamine and anhydrous tetrahydrofuran in step B3 is 10 mmol: 40-45 mmol: 100-120 mL.
[0024] As a further scheme of the present invention: the usage ratio of the intermediate 3, 2,2-dihydroxymethylpropionic acid, p-toluenesulfonic acid and xylene in step B4 is 10 mmol: 50-100 mmol: 0.1-0.3 g: 120-150 mL.
[0025] Beneficial effects of the present invention:
[0026] The present invention discloses a method for preparing microcrystalline glass by using coal gangue, comprising the steps of adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill for ball milling, drying, melting in a high-temperature furnace, and casting to obtain a microcrystalline glass green body, and placing the microcrystalline glass green body in a high-temperature furnace for heat preservation to obtain microcrystalline glass; the method uses coal gangue as the main raw material, realizes resource utilization of coal gangue, reduces environmental pollution caused by coal gangue, and reduces the production cost of microcrystalline glass; epoxy-modified carbon nanotubes are then added thereto to enhance the microstructural stability of the microcrystalline glass , which improves its mechanical strength and thermal stability, and improves the performance and life of the microcrystalline glass. Then, a hyperbranched refiner is added thereto, which not only improves the ball milling efficiency and reduces energy consumption, but also enables the coal gangue and epoxy-modified carbon nanotubes to evenly participate in the formation of microcrystalline glass, making the grains of the microcrystalline glass more uniform and fine, greatly improving its density, and strengthening the structure of the microcrystalline glass, thereby improving the growth and crystallization quality of the glass crystal phase, and promoting the rapid generation and stabilization of the crystal phase in the microcrystalline glass. Ultimately, the prepared microcrystalline glass has excellent mechanical strength, chemical stability, and excellent economic efficiency.
[0027] In the process of preparing microcrystalline glass, an epoxy-modified carbon nanotube is first prepared. First, multi-walled carbon nanotubes are oxidized by using nitric acid solution and hydrogen peroxide to introduce a large number of hydroxyl groups into the multi-walled carbon nanotubes to obtain oxidized carbon nanotubes. Then, the oxidized carbon nanotubes and epichlorohydrin are reacted. The hydroxyl groups on the oxidized carbon nanotubes react with the epoxy groups on the epichlorohydrin to undergo a ring-opening and ring-closing reaction, thereby introducing a large number of epoxy groups into the multi-walled carbon nanotubes to obtain epoxy-modified carbon nanotubes. Carbon nanotubes have a very high Young's modulus and excellent mechanical properties. After adding them to microcrystalline glass, the overall mechanical properties of the microcrystalline glass can be greatly improved. Moreover, since the epoxy-modified carbon nanotubes have a large number of epoxy groups, they can be connected to coal gangue powder in the form of chemical bonds, making the doping distribution of the multi-walled carbon nanotubes more uniform, so that the performance improvement effect of the multi-walled carbon nanotubes is best demonstrated.
[0028] In the process of preparing microcrystalline glass, a hyperbranched refiner is also prepared. The reaction of pyrene and bromine is used. Bromine is used as a brominating agent to introduce a large number of bromine atoms into pyrene to obtain intermediate 1. Then, intermediate 1 is reacted with eugenol. The bromine atoms on intermediate 1 react with the hydroxyl groups on eugenol, and a large number of alkenyl groups are introduced to obtain intermediate 2. Then, intermediate 2 is reacted with diethanolamine. The alkenyl groups on intermediate 2 react with -NH- on diethanolamine to form a Michael addition reaction. At the same time, a large number of hydroxyl groups are introduced to obtain intermediate 3. Then, intermediate 3 is reacted with 2,2-dihydroxymethylpropionic acid. The hydroxyl groups on intermediate 3 react with the carboxyl groups on 2,2-dihydroxymethylpropionic acid. The invention relates to a method for preparing a hyperbranched finesizer. The method comprises the following steps: introducing a large number of hydroxyl groups and continuously reacting with 2,2-dihydroxymethylpropionic acid to form a hyperbranched structure, thereby obtaining a hyperbranched finesizer. The hyperbranched finesizer has a high degree of branching, large steric hindrance, no entanglement between molecules, and contains a large number of hydroxyl groups at the ends. The hyperbranched finesizer can effectively adsorb onto the gangue powder, reduce the surface energy of the gangue powder, cause dislocation migration of the near-surface layer lattice, generate point or line defects, promote crack expansion and extension, and prevent the new cracks from healing again, so that the gangue powder can be fully refined, and the obtained microcrystalline glass has a dense structure, thereby greatly improving the mechanical properties and acid and alkali resistance of the microcrystalline glass. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Embodiment 1:
[0031] This embodiment is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0032] Step S1: 2 g of multi-walled carbon nanotubes with an average tube diameter of 80 nm and an average tube length of 20 μm and 40 mL of a nitric acid solution with a molar concentration of 3 mol / L are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 20 min at an ultrasonic frequency of 80 kHz, and then stirred for reaction at a temperature of 75° C. and a stirring rate of 300 r / min for 3 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is added to 30% hydrogen peroxide water by mass, and soaked at a temperature of 60° C. for 10 h, and then centrifuged. The precipitate is washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 80° C. for 2 h to obtain oxidized carbon nanotubes;
[0033] Step S2: 0.5 g of oxidized carbon nanotubes, 4 mL of epichlorohydrin and 40 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to 55° C. and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 2 h to obtain epoxy-modified carbon nanotubes;
[0034] Step S3: 10 mmol of pyrene and 100 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction at a temperature of -5°C and a stirring rate of 300 r / min for 20 min, and then 40 mmol of bromine was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the mixture was heated to 120°C and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to anhydrous ethanol, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 70°C for 2 h to obtain intermediate 1;
[0035] Step S4: 45mmol sodium hydroxide and 100mL deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The reaction was stirred for 15min at a temperature of 25°C and a stirring rate of 300r / min, and then 10mmol intermediate 1, 40mmol eugenol and 70mL N, N-dimethylformamide were added and the stirring reaction was continued for 1h. Then, the temperature was raised to 55°C and the stirring reaction was continued for 2h. After the reaction was completed, the reaction product was cooled to room temperature, and then allowed to stand for stratification. The organic phase was washed twice with distilled water, and then the solvent was removed by rotary evaporation to obtain intermediate 2;
[0036] Step S5: 10 mmol of intermediate 2, 40 mmol of diethanolamine and 100 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 25° C. and a stirring rate of 300 r / min for 25 min, and then the temperature was raised to 45° C. and the stirring reaction was continued for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 3;
[0037] Step S6: 10 mmol of intermediate 3, 50 mmol of 2,2-dihydroxymethylpropionic acid, 0.1 g of p-toluenesulfonic acid and 120 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at 25° C. and a stirring rate of 300 r / min for 25 min, and then the mixture is heated to 145° C. and stirred for reaction for 8 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The product is then added to anhydrous methanol, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at 50° C. for 4 h to obtain a hyperbranched refiner.
[0038] Step S7: weigh 20 parts of coal gangue, 0.1 parts of epoxy-modified carbon nanotubes, 0.03 parts of hyperbranched refiner and 40 parts of anhydrous ethanol according to weight parts, and set aside;
[0039] Step S8: adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill, ball milling for 2 hours at a ball milling rate of 300 r / min, then placing in a vacuum drying oven, drying at a temperature of 75° C. for 2 hours, then placing in a high-temperature furnace, melting at a temperature of 1400° C. for 2 hours, then pouring into a mold for casting, then annealing at a temperature of 550° C. for 1 hour, and then cooling with the furnace to obtain a microcrystalline glass green body;
[0040] Step S9: placing the glass-ceramic green body in a high-temperature furnace, keeping it at 650°C for 1 hour, then keeping it at 950°C for 1 hour, then keeping it at 1200°C for 1 hour, and then cooling it with the furnace to obtain the glass-ceramic.
[0041] Embodiment 2:
[0042] This embodiment is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0043] Step S1: 2 g of multi-walled carbon nanotubes with an average tube diameter of 80 nm and an average tube length of 20 μm and 45 mL of a nitric acid solution with a molar concentration of 3.5 mol / L are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 25 min at an ultrasonic frequency of 90 kHz, and then stirred for reaction at a temperature of 78° C. and a stirring rate of 350 r / min for 3.5 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is added to hydrogen peroxide with a mass fraction of 32%, and soaked at a temperature of 62° C. for 11 h, and then centrifuged. The precipitate is washed twice with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 2.5 h to obtain oxidized carbon nanotubes;
[0044] Step S2: 0.5 g of oxidized carbon nanotubes, 4.5 mL of epichlorohydrin and 45 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the temperature was raised to 58° C. and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 58° C. for 2.5 h to obtain epoxy-modified carbon nanotubes;
[0045] Step S3: 10 mmol of pyrene and 110 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for 25 min at a temperature of -2°C and a stirring rate of 350 r / min, and then 45 mmol of bromine was added dropwise while stirring, and the dropping rate was controlled to be 1 drop / s. After the addition was completed, the mixture was heated to 122°C and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to anhydrous ethanol, and then centrifuged. The precipitate was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 72°C for 2.5 h to obtain intermediate 1;
[0046] Step S4: 50 mmol of sodium hydroxide and 110 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 20 min, and then 10 mmol of intermediate 1, 42 mmol of eugenol and 75 mL of N,N-dimethylformamide were added and the stirring reaction was continued for 1.5 h. The mixture was then heated to 58° C. and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then allowed to stand for stratification. The organic phase was washed twice with distilled water, and then the solvent was removed by rotary evaporation to obtain intermediate 2;
[0047] Step S5: 10 mmol of intermediate 2, 42 mmol of diethanolamine and 110 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 30 min, and then the mixture was heated to 48° C. and stirred for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 3;
[0048] Step S6: 10 mmol of intermediate 3, 75 mmol of 2,2-dihydroxymethylpropionic acid, 0.2 g of p-toluenesulfonic acid and 135 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 28° C. and a stirring rate of 350 r / min for 30 min, and then the mixture is heated to 148° C. and the stirring reaction is continued for 9 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The product is then added to anhydrous methanol, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at 52° C. for 4.5 h to obtain a hyperbranched refiner;
[0049] Step S7: weigh 25 parts of coal gangue, 0.9 parts of epoxy-modified carbon nanotubes, 0.35 parts of hyperbranched refiner and 42 parts of anhydrous ethanol according to weight parts for later use;
[0050] Step S8: adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill, ball milling for 2.5 hours at a ball milling rate of 350 r / min, then placing in a vacuum drying oven, drying at a temperature of 78° C. for 2.5 hours, then placing in a high-temperature furnace, melting at a temperature of 1450° C. for 2.5 hours, then pouring into a mold for casting, then annealing at a temperature of 575° C. for 1.5 hours, and then cooling with the furnace to obtain a microcrystalline glass green body;
[0051] Step S9: Place the glass-ceramic green body in a high-temperature furnace, keep it at 675°C for 1.2 hours, then keep it at 975°C for 1.2 hours, then keep it at 1250°C for 1.2 hours, and then cool it with the furnace to obtain the glass-ceramic.
[0052] Embodiment 3:
[0053] This embodiment is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0054] Step S1: 2 g of multi-walled carbon nanotubes with an average tube diameter of 80 nm and an average tube length of 20 μm and 50 mL of a nitric acid solution with a molar concentration of 4 mol / L are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 30 min at an ultrasonic frequency of 100 kHz, and then stirred for reaction for 4 h at a temperature of 80° C. and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is added to hydrogen peroxide with a mass fraction of 35%, and soaked at a temperature of 65° C. for 12 h, and then centrifuged. The precipitate is washed three times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 90° C. for 3 h to obtain oxidized carbon nanotubes;
[0055] Step S2: 0.5 g of oxidized carbon nanotubes, 5 mL of epichlorohydrin and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain epoxy-modified carbon nanotubes;
[0056] Step S3: 10 mmol of pyrene and 120 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction at a temperature of 0°C and a stirring rate of 400 r / min for 30 min, and then 50 mmol of bromine was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the mixture was heated to 125°C and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to anhydrous ethanol, and then centrifuged. The precipitate was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 3 h to obtain intermediate 1;
[0057] Step S4: 55mmol sodium hydroxide and 120mL deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30°C and a stirring rate of 400r / min for 25min, and then 10mmol intermediate 1, 45mmol eugenol and 80mL N,N-dimethylformamide were added and the stirring reaction was continued for 2h. The mixture was then heated to 60°C and the stirring reaction was continued for 3h. After the reaction was completed, the reaction product was cooled to room temperature, and then allowed to stand for stratification. The organic phase was washed with distilled water for 3 times, and then the solvent was removed by rotary evaporation to obtain intermediate 2;
[0058] Step S5: 10 mmol of intermediate 2, 45 mmol of diethanolamine and 120 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 35 min, and then the temperature was raised to 50° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 3;
[0059] Step S6: 10 mmol of intermediate 3, 100 mmol of 2,2-dihydroxymethylpropionic acid, 0.3 g of p-toluenesulfonic acid and 150 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 30° C. and a stirring rate of 400 r / min for 35 min, and then the mixture is heated to 150° C. and stirred for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The product is then added to anhydrous methanol, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at 55° C. for 5 h to obtain a hyperbranched refiner.
[0060] Step S7: weigh 30 parts of coal gangue, 1.7 parts of epoxy-modified carbon nanotubes, 0.7 parts of hyperbranched refiner and 45 parts of anhydrous ethanol according to weight parts, and set aside;
[0061] Step S8: adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill, ball milling for 3 hours at a ball milling rate of 400 r / min, then placing in a vacuum drying oven, drying at a temperature of 80° C. for 3 hours, then placing in a high-temperature furnace, melting at a temperature of 1500° C. for 3 hours, then pouring into a mold for casting, then annealing at a temperature of 600° C. for 2 hours, and then cooling with the furnace to obtain a glass-ceramic green body;
[0062] Step S9: Place the glass-ceramic green body in a high-temperature furnace, keep it at 700°C for 1.5 hours, then keep it at 1000°C for 1.5 hours, then keep it at 1300°C for 1.5 hours, and then cool it with the furnace to obtain glass-ceramic.
[0063] Comparative Example 1:
[0064] This comparative example is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0065] Step S1: weigh 30 parts of coal gangue and 45 parts of anhydrous ethanol according to weight and set aside;
[0066] Step S2: adding coal gangue and anhydrous ethanol into a ball mill, ball milling for 3 hours at a ball milling rate of 400 r / min, then placing in a vacuum drying oven, drying at a temperature of 80° C. for 3 hours, then placing in a high-temperature furnace, melting at a temperature of 1500° C. for 3 hours, then pouring into a mold for casting, then annealing at a temperature of 600° C. for 2 hours, and then cooling with the furnace to obtain a microcrystalline glass green body;
[0067] Step S3: placing the glass-ceramic green body in a high-temperature furnace, keeping it at 700°C for 1.5 hours, then keeping it at 1000°C for 1.5 hours, then keeping it at 1300°C for 1.5 hours, and then cooling it with the furnace to obtain the glass-ceramic.
[0068] Comparative Example 2:
[0069] This comparative example is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0070] Step S1: 2 g of multi-walled carbon nanotubes with an average tube diameter of 80 nm and an average tube length of 20 μm and 50 mL of a nitric acid solution with a molar concentration of 4 mol / L are added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 30 min at an ultrasonic frequency of 100 kHz, and then stirred for reaction for 4 h at a temperature of 80° C. and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is added to hydrogen peroxide with a mass fraction of 35%, and soaked at a temperature of 65° C. for 12 h, and then centrifuged. The precipitate is washed three times with anhydrous ethanol and distilled water in sequence, and then placed in a vacuum drying oven and dried at a temperature of 90° C. for 3 h to obtain oxidized carbon nanotubes;
[0071] Step S2: 0.5 g of oxidized carbon nanotubes, 5 mL of epichlorohydrin and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer and a thermometer, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature was raised to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 3 h to obtain epoxy-modified carbon nanotubes;
[0072] Step S3: weigh 30 parts of coal gangue, 1.7 parts of epoxy-modified carbon nanotubes and 45 parts of anhydrous ethanol according to weight and set aside;
[0073] Step S4: adding coal gangue, epoxy-modified carbon nanotubes and anhydrous ethanol into a ball mill, ball milling for 3 hours at a ball milling rate of 400 r / min, then placing in a vacuum drying oven, drying at a temperature of 80° C. for 3 hours, then placing in a high-temperature furnace, melting at a temperature of 1500° C. for 3 hours, then pouring into a mold for casting, then annealing at a temperature of 600° C. for 2 hours, and then cooling with the furnace to obtain a microcrystalline glass green body;
[0074] Step S5: placing the glass-ceramic green body in a high-temperature furnace, keeping it at 700°C for 1.5 hours, then keeping it at 1000°C for 1.5 hours, then keeping it at 1300°C for 1.5 hours, and then cooling it with the furnace to obtain the glass-ceramic.
[0075] Comparative Example 3:
[0076] This comparative example is a method for preparing glass-ceramics using coal gangue, comprising the following steps:
[0077] Step S1: 10 mmol of pyrene and 120 mL of nitrobenzene were added to a three-necked flask equipped with a stirrer, a thermometer and a constant pressure dropping funnel, and the mixture was stirred for reaction at a temperature of 0°C and a stirring rate of 400 r / min for 30 min, and then 50 mmol of bromine was added dropwise while stirring, and the dropping rate was controlled to be 2 drops / s. After the addition was completed, the mixture was heated to 125°C and the stirring reaction was continued for 10 h. After the reaction was completed, the reaction product was cooled to room temperature, and then added to anhydrous ethanol, and then centrifuged. The precipitate was washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75°C for 3 h to obtain intermediate 1;
[0078] Step S2: 55 mmol sodium hydroxide and 120 mL deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 25 min, and then 10 mmol intermediate 1, 45 mmol eugenol and 80 mL N, N-dimethylformamide were added and the stirring reaction was continued for 2 h. The mixture was then heated to 60° C. and the stirring reaction was continued for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then allowed to stand for stratification. The organic phase was washed with distilled water 3 times, and then the solvent was removed by rotary evaporation to obtain intermediate 2;
[0079] Step S3: 10 mmol of intermediate 2, 45 mmol of diethanolamine and 120 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 35 min, and then the temperature was raised to 50° C. and the stirring reaction was continued for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain intermediate 3;
[0080] Step S4: 10 mmol of intermediate 3, 100 mmol of 2,2-dihydroxymethylpropionic acid, 0.3 g of p-toluenesulfonic acid and 150 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 30° C. and a stirring rate of 400 r / min for 35 min, and then the mixture is heated to 150° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then the solvent is removed by rotary evaporation. The product is then added to anhydrous methanol, and then vacuum filtered. The filter cake is placed in a vacuum drying oven and dried at 55° C. for 5 h to obtain a hyperbranched refiner;
[0081] Step S5: weigh 30 parts of coal gangue, 0.7 parts of hyperbranched refiner and 45 parts of anhydrous ethanol according to weight parts for later use;
[0082] Step S6: adding coal gangue, hyperbranched refiner and anhydrous ethanol into a ball mill, ball milling for 3 hours at a ball milling rate of 400 r / min, then placing in a vacuum drying oven, drying at a temperature of 80° C. for 3 hours, then placing in a high-temperature furnace, melting at a temperature of 1500° C. for 3 hours, then pouring into a mold for casting, then annealing at a temperature of 600° C. for 2 hours, and then cooling with the furnace to obtain a glass-ceramic green body;
[0083] Step S7: placing the glass-ceramic green body in a high-temperature furnace, keeping it at 700°C for 1.5 hours, then keeping it at 1000°C for 1.5 hours, then keeping it at 1300°C for 1.5 hours, and then cooling it with the furnace to obtain the glass-ceramic.
[0084] The coal gangue of Examples 1-3 and Comparative Examples 1-3 were subjected to component analysis, and the analysis results are shown in the following table:
[0085]
[0086] The performance of the glass-ceramics of Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in the following table:
[0087]
[0088] Among them, the flexural strength test method is: use the three-point bending method to test the flexural strength of a microcrystalline glass sample with a size of 5mm×5mm×45mm, the fulcrum span is 30mm, and the loading speed is 1mm / min; the acid resistance test method is: place a microcrystalline glass sample with a diameter of 14mm and a height of 2.5mm in a sulfuric acid solution with a mass concentration of 1% and soak it for 24 hours, and then measure the mass loss rate; the alkali resistance test method is: place a microcrystalline glass sample with a diameter of 14mm and a height of 2.5mm in a sodium hydroxide solution with a mass concentration of 1% and soak it for 24 hours, and then measure the mass loss rate.
[0089] Referring to the data in the above table, it can be seen that adding epoxy-modified carbon nanotubes and hyperbranched refiners can greatly improve the mechanical properties and acid-base resistance of the microcrystalline glass, so that the microcrystalline glass of the present application has excellent mechanical properties and acid-base resistance.
[0090] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0091] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing glass-ceramics using coal gangue, characterized in that: The following steps are involved: Step 1: Weigh 20-30 parts of coal gangue, 0.1-1.7 parts of epoxy-modified carbon nanotubes, 0.03-0.7 parts of hyperbranched refiner and 40-45 parts of anhydrous ethanol according to weight, and set aside; Step 2: adding coal gangue, epoxy-modified carbon nanotubes, hyperbranched refiner and anhydrous ethanol into a ball mill, milling for 2-3 hours at a ball milling rate of 300-400 r / min, then placing in a vacuum drying oven, drying at a temperature of 75-80°C for 2-3 hours, then placing in a high-temperature furnace, melting at a temperature of 1400-1500°C for 2-3 hours, then pouring into a mold for casting, then annealing at a temperature of 550-600°C for 1-2 hours, and then cooling with the furnace to obtain a microcrystalline glass green body; Step 3: placing the glass-ceramic green body in a high temperature furnace, keeping it at a temperature of 650-700° C. for 1-1.5 hours, then keeping it at a temperature of 950-1000° C. for 1-1.5 hours, then keeping it at a temperature of 1200-1300° C. for 1-1.5 hours, and then cooling it with the furnace to obtain glass-ceramic; Wherein, the epoxy-modified carbon nanotubes are prepared by the following steps: Step A1: ultrasonically dispersing multi-walled carbon nanotubes and nitric acid solution, and then stirring to react. After the reaction is completed, the reaction product is cooled and then centrifuged. The precipitate is added to hydrogen peroxide and soaked, and then centrifuged. The precipitate is washed and dried to obtain oxidized carbon nanotubes; Step A2: stirring the oxidized carbon nanotubes, epichlorohydrin and deionized water for reaction, cooling the reaction product after the reaction is completed, and then centrifuging it, washing and drying the precipitate to obtain epoxy-modified carbon nanotubes; The hyperbranched refiner is prepared by the following steps: Step B1: stirring pyrene and nitrobenzene for reaction, then adding bromine dropwise while stirring, and continuing to stir the reaction after the addition is complete. After the reaction is complete, the reaction product is cooled, then added to anhydrous ethanol, and then centrifuged, and the precipitate is washed and dried to obtain intermediate 1; Step B2: Sodium hydroxide and deionized water are stirred for reaction, and then intermediate 1, eugenol and N,N-dimethylformamide are added and stirred for reaction. After the reaction is completed, the reaction product is cooled, and then allowed to stand for stratification, and the organic phase is washed and then rotary evaporated to obtain intermediate 2; Step B3: stirring the intermediate 2, diethanolamine and anhydrous tetrahydrofuran for reaction, cooling the reaction product after the reaction is completed, and then rotary evaporating to obtain the intermediate 3; Step B4: Stir and react the intermediate 3, 2,2-dihydroxymethylpropionic acid, p-toluenesulfonic acid and xylene. After the reaction, cool the reaction product, then rotary evaporate it, add it to anhydrous methanol, and then vacuum filter it, dry the filter cake to obtain a hyperbranched refiner.
2. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The usage ratio of the multi-walled carbon nanotubes and the nitric acid solution in step A1 is 2 g: 40-50 mL.
3. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The average tube diameter of the multi-walled carbon nanotubes in step A1 is 80 nm, and the average tube length is 20 μm; the molar concentration of the nitric acid solution is 3-4 mol / L; and the mass fraction of the hydrogen peroxide is 30-35%.
4. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The dosage ratio of the oxidized carbon nanotubes, epichlorohydrin and deionized water in step A2 is 0.5 g: 4-5 mL: 40-50 mL.
5. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The usage ratio of the pyrene, nitrobenzene and bromine in step B1 is 10mmol:100-120mL:40-50mmol.
6. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The usage ratio of the sodium hydroxide, deionized water, intermediate 1, eugenol and N,N-dimethylformamide in step B2 is 45-55mmol:100-120mL:10mmol:40-45mmol:70-80mL.
7. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The usage ratio of the intermediate 2, diethanolamine and anhydrous tetrahydrofuran in step B3 is 10 mmol: 40-45 mmol: 100-120 mL.
8. The method for preparing glass-ceramics using coal gangue according to claim 1, characterized in that: The usage ratio of the intermediate 3, 2,2-dihydroxymethylpropionic acid, p-toluenesulfonic acid and xylene in step B4 is 10 mmol: 50-100 mmol: 0.1-0.3 g: 120-150 mL.
Citation Information
Patent Citations
Symmetric discotic pyrene compounds and preparation method thereof
CN102503854A
Preparation method of microcrystalline glass taking coal gangue and fluorapatite as raw materials
CN111018355A